2013
DOI: 10.1007/s12630-013-9903-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of an online three-dimensional model improves performance in ultrasound scanning of the spine: a randomized trial

Abstract: Purpose The use of ultrasound for neuraxial blockade is a new application of technology that is rapidly becoming accepted as a standard of care. This new skill has shown to improve success, but it is a challenge to teach. To assist with teaching the use of ultrasound in regional anesthesia of the lumbar spine, we have developed an interactive educational model (http://pie.med.utoronto.ca/vspine or http://www.usra.ca/vspine.php). In this study, we aimed to determine whether use of this model for a two-week peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…A total of 24 studies (1757 participants) [11,24,26-28,30-32, 34-37,39,41-44,46-48,50-53] assessed knowledge as the primary outcome. Of them, 6 studies focused on postregistration health professionals [30,42,46,47,50,53] and all others focused on preregistration health professionals.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 studies (1757 participants) [11,24,26-28,30-32, 34-37,39,41-44,46-48,50-53] assessed knowledge as the primary outcome. Of them, 6 studies focused on postregistration health professionals [30,42,46,47,50,53] and all others focused on preregistration health professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a remarkable improvement has been achieved in teaching ultrasound skills using an online three-dimensional model. In this study by Niazi et al , residents randomized to a three-dimensional online module identified key bony structures better than the control group during pre-procedural two-dimensional ultrasound albeit; no statistical difference was achieved among the groups (20). In our technology development efforts, we have determined that real-time volumetric imaging of a spine model using a custom handheld device is achievable and is a viable innovative technology.…”
Section: Discussionmentioning
confidence: 83%
“…In this way, the material is more likely to be learned if it is reviewed just prior to performing the procedure. 19 The simulator allows the user to practice the probe movements required to obtain optimal ultrasound views and perform landmarking of the interlaminar space. However, this simulator does not provide haptic feedback, nor does it test psychomotor skills.…”
Section: Discussionmentioning
confidence: 99%